Age-specific reference ranges for serum testosterone and androstenedione concentrations in women measured by liquid chromatography-tandem mass spectrometry - Haring, Robin; Hannemann, Anke; John, Ulrich; Radke, Dörte; Nauck, Matthias; Wallaschofski, Henri; Owen, Laura; Adaway, Jo; Keevil, Brian G; Brabant, Georg (The journal of clinical endocrinology and metabolism, 2012)
RIA-based sex hormone measurements offer only limited precision and specificity in the low concentration range of women. Therefore, we aimed to establish age-specific reference ranges for serum sex hormone concentrations in women using mass spectrometry and quantile regression. Data from 985 women aged 20-80 yr, recruited for the prospective Study of Health in Pomerania, were included in the analyses. Quantile regressions models were performed to calculate the age-specific 2.5th and 97.5th percentiles for sex hormone concentrations in women. Serum total testosterone (TT) and androstenedione (AD) concentrations were measured by liquid chromatography-tandem mass spectrometry. Measured concentrations of SHBG and TT were used to calculate free testosterone (free T). TT, AD, and free T concentrations showed a distinct age-related decline across 10-yr age groups (one way ANOVA P < 0.001). Sex hormone reference ranges for TT, AD, and free T were determined across each single year of age and for 10-yr age groups. Reference ranges over the whole age range of 20-80 yr were 0.35-1.97 nmol/liter for TT, 0.89-4.56 nmol/liter for AD, and 0.0025-0.0253 nmol/liter for free T. Separate reference ranges were provided for pre- and postmenopausal women as well as after inclusion of women using oral contraceptives or hormone therapy (n = 1357). This is the first study to establish age-specific reference ranges for liquid chromatography-tandem mass spectrometry-measured TT and AD and calculated free T concentrations based on quantile regression analyses, accurately accounting for the observed low concentration range and the strong age dependency of these sex hormones in women.